Simulation of Greenland mass balance evolution until 2100 - Peano, Daniele (Università Ca' Foscari Venezia, 2016)
The evolution of the Greenland ice sheet mass balance has a potential impact on the regional and global climate. Moreover, the runoff from the Greenland ice sheet into the nearby ocean and its evolution are not well known, despite their potential impacts on ocean circulation. For this reason, this study investigates the evolution of Greenland mass balance and runoff during the 20th and 21st century by means of two thermo-mechanical ice sheet-ice shelves models. Transient simulations forced with the climate simulated from seven CMIP5 models, are performed, and the evolution of surface mass balance and runoff for the entire ice-sheet and for seven drainage basins are analyzed. The ability of one of the two thermo-mechanical ice sheet-ice shelves models in simulating basal melting and calving is investigated, in order to close the Greenland ice sheet mass balance. The simulated surface mass balance exhibits values in a wide range in the 20th century (362 Gt/yr to -131 Gt/yr). The simulated surface mass balance decreases in time reaching values ranging from 59 Gt/yr to -436 Gt/yr for the RCP 4.5 simulations, and from -591 Gt/yr to -1857 Gt/yr for the RCP 8.5 simulations by 2100. This decrease is characterized by an acceleration after the 2030s, more evident for the RCP 8.5 scenario, and the strongest reductions are simulated in the northern regions under both scenarios. The simulated present-day (1980–1999) runoff ranges from 0.78 mm SLE/yr to 0.86 mm SLE/yr, and at the end of the 21st century (2081–2100) the runoff is projected to increase to 1.25 mm SLE/yr to 1.51 mm SLE/yr (2.36 mm SLE/yr to 2.94mm SLE/yr) under a RCP 4.5 (RCP 8.5) scenario. On regional scale, the highest amount of runoff is found in the northern and western basins, and the north-western one presents the largest values at the end of the 21st century, up to 0.68 mm SLE/yr under a RCP 8.5 scenario. Finally, the simulated basal melting produced by one of the two thermo-mechanical ice sheet-ice shelves models exhibits small values compared to the ...